Underwater archaeology and submerged landscapes in western Australia. (27th June 2018) - Benjamin, Jonathan; O'Leary, Michael; Ward, Ingrid; Hacker, Jorg; Ulm, Sean; Veth, Peter; Holst, Mads; McDonald, Jo; Ross, Peter J.; Bailey, Geoff
Abstract : This research aims to explore the submerged landscapes of the Pilbara of western Australia, using predictive archaeological modelling, airborne LiDAR, marine acoustics, coring and diver survey. It includes excavation and geophysical investigation of a submerged shell midden in Denmark to establish guidelines for the underwater discovery of such sites elsewhere.